Safety and psychological impact of sailing adventure therapy among Veterans with substance use disorders. (October 2018) - Marchand, W.R.; Klinger, W.; Block, K.; VerMerris, S.; Herrmann, T.S.; Johnson, C.; Shubin, E.; Sheppard, S.
Highlights: Sailing Adventure Therapy (SAT) is perceived as a positive and calming activity among Veterans with substance use disorders. SAT does not increase anxiety or negative affect among this population. Preliminary evidence suggests that SAT may increase psychological flexibility and enhance treatment response. Further studies are indicated to determine if SAT can be developed as a complementary intervention for Veterans. Abstract: Objectives: Many Veterans suffer from substance use disorders (SUDs). Treatment challenges include poor treatment engagement and high relapse rates. Complementary interventions have the potential to enhance both. This study was a preliminary evaluation of sailing adventure therapy (SAT) for this population. Design: Retrospective chart review. Participants in the intervention were 22 Veterans (20 male, 2 female) aged 22–65 who entered a Veterans Administration residential SUD treatment program. All subjects had two or more SUDs, and many had psychiatric (95%) and/or medical (77%) comorbidities. The age, gender and diagnosis-matched control group (n = 22) received residential SUD treatment as usual (TAU) in the same program but without SAT. Setting: Residential SUD treatment program at a Veterans Administration Medical Center. Intervention: Sailing adventure therapy. Main Outcome Measures: Positive and Negative Affect Schedule (PANAS), State Trait Anxiety Inventory six-item short form (STAI: Y-6 item), Acceptance and Action Questionnaire II (AAQ II), Five Facet Mindfulness Questionnaire (FFMQ) and a locally developed patient survey. Outcome comparison among SAT plus TAU group versus TAU – only group included measures of successful completion of residential SUD treatment program as well as psychiatric hospitalizations and/or residential SUD treatment program readmissions within 12 months. Results: Neither physical injuries nor increases in anxiety or negative affect occurred, as measured by the PANAS (positive change, p = 0.351; negative change, p = 0.605) and the STAI: Y-6 item (p = 0.144) respectively. There was no significant change in FFMQ (p = 0.580) but a significant increase occurred in AAQ II scores (p = 0.036) indicating an increase in psychological flexibility. Survey responses indicated the participants perceived the experience to be both pleasurable and calming. The preliminary outcome evaluation revealed a significant between-group difference (X 2 = 5.34, DF = 1, p = 0.02, r = 0.35) indicating participating in SAT was associated with a greater likelihood of successfully completing residential SUD treatment. However, there were no significant between-group differences in number of psychiatric hospitalizations (X 2 = 1.09, DF = 1, p = 0.29, r = 0.16) or residential substance abuse treatment program readmissions (X 2 = 0.23, DF = 1, p = 0.64, r = 0.07) in the 12 months after discharge from the program. Conclusions: Preliminary evidence suggests that SAT is physically safe and not associated with increased anxiety or negative affect. Participant's perceptions of the experience were positive. Preliminary outcome measures suggest associations between participation in SAT and increased psychological flexibility as well as successful completion of a residential SUD treatment program. Further research is indicated to determine whether SAT may be developed as an effective complementary intervention for Veterans with SUDs.